How organisations can affect employees' intention to manage enterprise-specific knowledge through informal mentoring: a vignette study. Issue 7 (9th July 2020) - Roobol, Conny J.J.; Koster, Ferry
Abstract : Purpose: The purpose of this study is to examine the role of organisational conditions and workplace characteristics in midcareer and senior employees' intention to volitionally provide career support to junior organisational members, their protégés. Design/methodology/approach: Hypotheses are tested using multilevel linear modelling on a heterogeneous sample of Dutch employees ages 29 to 69 who participated in a vignette study in the autumn of 2017. Findings: In line with the hypotheses, the findings of this study show that volitional (informal) mentoring is positively related to an organisation's endorsement of intrinsic values (e.g. learning opportunities) and negatively to the presence of hindrance demands (e.g. time pressure). Practical implications: Practitioners could facilitate co-mentor consultation, employ autonomy-supportive direct supervisors and fulfil psychological contract obligations by providing job security and learning opportunities. Organisations could also lower time pressures through job carving. Originality/value: This study extends extant mentoring research by combining insights from perceived organisational support (POS) and self-determination theory (SDT) to examine the role organisational conditions and workplace characteristics play in aiding or hindering volitional mentoring. It enriches extant knowledge management studies on the link between organisational aspects and (intended) knowledge sharing behaviour by showing that similar organisational motivators predict volitional mentoring, thereby launching a call to study knowledge management through volitional mentoring using a SDT- and POS-based lens. A methodological novelty is the reliance on a vignette study.